Development and physicochemical characteristics of multicomponent freeze-dried snacks obtained with blackcurrant pomace powder and calcium ions as structuring agents - Magdalena Karwacka
Consumers seek healthy and sustainable products, whereas the food industry faces the challenge of processing by-products management. The application of fruit pomace as an additive could be a solution addressing the needs of both consumers and producers. The research objective has been to assess the effect of dried blackcurrant pomace powder (BP) and calcium ions in varied concentration on the physicochemical properties of multicomponent freeze-dried snacks as compared to the influence of low-methoxyl pectin (LMP). The snacks were prepared using varied content of BP (1, 3, 5%) and calcium lactate (0, 0.01, 0.05%). Water content and activity, hygroscopic properties, structure, texture, colour, polyphenols content (TPC), and antioxidant activity were analysed. The addition of BP resulted in lowering water activity and porosity. The microstructure of the snacks consisted of a large number of small and unevenly distributed pores. Consequently, the reduction of hygroscopic properties with the growing amount of BP was observed. Applied additives strengthened the structure and caused changes in compression curves indicating enhanced hardness and crispiness. The effect given by 5% of BP was comparable to that obtained with 0.5% of LMP. Additionally, blackcurrant pomace infusion increased TPC and enhanced antioxidant activity but it also caused significant changes in the colour of the snacks. Overall, obtained results have shown that dried blackcurrant pomace powder (BP) can be successfully applied as a food additive supporting stability, texture, and bioactive compounds content, thus fortifying the physicochemical properties of freeze-dried fruit and vegetable snacks.